Representation of the Citizen-initiated White Flag movement in Malaysian newspapers - Su Hie, Ting; Angelina Nicollina Felix, Hospi (UKM Press, 2025)
This study analysed Malaysian English and Malay newspaper coverage of the citizen-led White Flag (WF) movement using the Discourse Historical Approach. The movement involved people in need hanging a white cloth to request community aid. Analysis of 87 articles in 10 newspapers published in June July 2021 showed that Malays were most frequently portrayed as needing help, followed by Chinese, Indians, Indigenous people and foreigners. Malay newspapers tended to depict more female recipients and male helpers compared to English newspapers. Across all newspapers, aid was mostly attributed to politicians, government agencies and individuals, and recipients were commonly framed as grateful but distressed rather than exploitative. Most articles legitimised WF as a timely citizen response, while a few highlighted abuse of aid. Minor counter-arguments questioned faith, government capability or personal resilience. Helper perspectives dominated over the voices of those in need. Newspapers used direct speech to personalise suffering and indirect speech to generalise collective responsibility. Modal verbs expressing mitigation and intensification appeared in almost equal measure, with Malay articles stressing duty while English reports conveyed contingency. The findings show how newspapers framed need, aid and responsibility through ethnic, gendered and moral lenses.